Seasonal dynamics of air temperature, snow storage and soil freezing in Central part of the East European Plain - I. M. Kitaev; V. A. Ableeva; Z. A. Asainova; A. S. Zheltukhin; E. D. Korobov (Лëд и снег)
The main objective of the research was to assess a nature of contingency in the seasonal course between char‑ acteristics of the soil thermal regime, surface air temperature, and snow cover, as well as to determine typical situations of their interaction. The investigation was based on results of the three‑year field observations per‑ formed in the Central part of the East European Plain. A degree of influence of different woody vegetation on the snow cover distribution under local homogeneity of the air temperature has been found as the following: maximal values of snow storages in the larch forests exceed similar ones on open sites and in the pine forests by 11‑25%. Inter‑annual changes of the soil temperature in areas with different vegetation were revealed to be very similar: differences in the temperature at depths of 10‑40 cm did not exceed 0.5‑1.0 °С. Phases of the soil temperature seasonal variations were isolated, and they were found to be closely related to changes in the sur‑ face air temperature and snow depths. During the period when the snow cover is steady (in winters), the soil temperature at a depth of 10‑40 cm becomes stable almost everywhere within the range from +1.0 to −1.0 °C. This suggests that in this period it does not depend on the landscape conditions, changes in the snow depth, and fluctuations in the surface air temperature. Thus, we make a conclusion that trends in multi‑year course of the soil temperature are primarily determined by variability of the surface air temperature during autumn and spring periods that may be also true for winters similar to mean ones in the center of the East European Plain.